The Influence of Extraversion and Neuroticism on Self-Esteem and Life Satisfaction Mediated by Facebook use Among Thai Millennials - Suebsumrarn, Pimchanok; Varma, Parvathy (Scholar: Human Sciences, 2019)
Facebook is the number one social networking site in the world that people engage in the most. Its popularity has reached epidemic proportions and it leaves many questions unanswered as to whether it is good or bad for users’ psychological health, especially for Millennials who engage in Facebook more than any other activity in their lives. The current investigation attempted to explore the direct and indirect influences of the personality traits of extraversion and neuroticism on self-esteem and life satisfaction, being mediated by Facebook use among Thai Millennials. The results indicate that extraversion and neuroticism showed no significant indirect influences on the self-esteem and life satisfaction of Thai Millennials, being mediated by their Facebook use. However, both extraversion and neuroticism were found to have positive direct relationships with self-esteem and life satisfaction. Moreover, there is a positive correlation between Facebook use and extraversion but not with neuroticism. Additionally, the amount of Facebook use has no link to either self-esteem or life satisfaction and that using Facebook does not change how Thai Millennials feel about themselves and their state of life satisfaction.